EULAR evidence-based recommendations for the management of fibromyalgia syndrome. Issue 4 (20th July 2007) - Carville, S F; Arendt-Nielsen, S; Bliddal, H; Blotman, F; Branco, J C; Buskila, D; Da Silva, J A P; Danneskiold-Samsøe, B; Dincer, F; Henriksson, C; Henriksson, K G; Kosek, E; et al.
Abstract : Objective: To develop evidence-based recommendations for the management of fibromyalgia syndrome. Methods: A multidisciplinary task force was formed representing 11 European countries. The design of the study, including search strategy, participants, interventions, outcome measures, data collection and analytical method, was defined at the outset. A systematic review was undertaken with the keywords "fibromyalgia", "treatment or management" and "trial". Studies were excluded if they did not utilise the American College of Rheumatology classification criteria, were not clinical trials, or included patients with chronic fatigue syndrome or myalgic encephalomyelitis. Primary outcome measures were change in pain assessed by visual analogue scale and fibromyalgia impact questionnaire. The quality of the studies was categorised based on randomisation, blinding and allocation concealment. Only the highest quality studies were used to base recommendations on. When there was insufficient evidence from the literature, a Delphi process was used to provide basis for recommendation. Results: 146 studies were eligible for the review. 39 pharmacological intervention studies and 59 non-pharmacological were included in the final recommendation summary tables once those of a lower quality or with insufficient data were separated. The categories of treatment identified were antidepressants, analgesics, and "other pharmacological" and exercise, cognitive behavioural therapy, education, dietary interventions and "other non-pharmacological". In many studies sample size was small and the quality of the study was insufficient for strong recommendations to be made. Conclusions: Nine recommendations for the management of fibromyalgia syndrome were developed using a systematic review and expert consensus.